A biological indicator of inorganic arsenic exposure using the sum of urinary inorganic arsenic and monomethylarsonic acid concentrations. Issue 2 (25th May 2016) - Hata, Akihisa; Kurosawa, Hidetoshi; Endo, Yoko; Yamanaka, Kenzo; Fujitani, Noboru; Endo, Ginji
Abstract : Objectives: The sum of urinary inorganic arsenic (iAs), monomethylarsonic acid (MMA), and dimethylarsinic acid (DMA) concentrations is used for the biological monitoring of occupational iAs exposure. Although DMA is a major metabolite of iAs, it is an inadequate index because high DMA levels are present in urine after seafood consumption. We estimated the urinary iAs+MMA concentration corresponding to iAs exposure. Methods: We used data from two arsenic speciation analyses of urine samples from 330 Bangladeshi with oral iAs exposure and 172 Japanese workers without occupational iAs exposure using high‐performance liquid chromatography with inductively coupled plasma mass spectrometry. Results: iAs, MMA, and DMA, but not arsenobetaine (AsBe), were detected in the urine of the Bangladeshi subjects. The correlation between iAs+MMA+DMA and iAs+MMA was obtained as log (iAs+MMA) = 1.038 log (iAs+MMA+DMA) −0.658. Using the regression formula, the iAs+MMA value was calculated as 2.15 and 7.5 μg As/l, corresponding to 3 and 10 μg As/m 3 of exposures, respectively. In the urine of the Japanese workers, arsenic was mostly excreted as AsBe. We used the 95 th percentile of iAs+MMA (12.6μg As/l) as the background value. The sum of the calculated and background values can be used as a biological indicator of iAs exposure. Conclusions: We propose 14.8 and 20.1 μg As/l of urinary iAs+MMA as the biological indicators of 3 and 10 μg As/m 3 iAs exposure, respectively.